Controllable Synthesis of Na3V2(PO4)3/C Nanofibers as Cathode Material for Sodium-Ion Batteries by Electrostatic Spinning - Wu, Ling; Hao, Yueying; Shi, Shaonan; Zhang, Xiaoping; Li, Huacheng; Sui, Yulei; Yang, Liu; Zhong, Shengkui (Frontiers in Chemistry, 2018)
Na3V2(PO4)3/C nanofibers are prepared by a pre-reduction assisted electrospinning method. In order to maintain the perfect fibrous architecture of the Na3V2(PO4)3/C products after calcining, a series of heat treatment parameters are studied in detail. It is found that the heat treatment process shows important influences on the morphology and electrochemical performance of Na3V2(PO4)3/C composite nanofibers. Under the calcining conditions of 800 °C for 10 h with a heating rate of 2.5 °C min-1, the well-crystallized uniform Na3V2(PO4)3/C nanofibers with excellent electrochemical performances is successfully obtained. The initial discharge specific capacities of the sample at 0.05C, 1C and 10C are 114.0, 106.0 and 77.9 mAh g-1, respectively. The capacity retention still remains 97.0% after 100 cycles at 0.05C. This smooth, uniform and continuous Na3V2(PO4)3/C composite nanofibers prepared by simple electrospinning method, is expected to be a superior cathode material for sodium-ion batteries.